Small for gestational age and perinatal mortality at term: An audit in a Dutch national cohort study. (August 2017) - Eskes, Martine; Waelput, Adja J.M.; Scherjon, Sicco A.; Bergman, Klasien A.; Abu-Hanna, Ameen; Ravelli, Anita C.J.
Abstract: Objective: To assess the underlying risk factors for perinatal mortality in term born small for gestational age infants. Study design: We performed a population based nationwide cohort study in the Netherlands of 465, 532 term born infants from January 2010 to January 2013. Logistic regression analyses were performed. Also audit results were studied for detailed care information. Results: We studied 162 small for gestational age infants who died in the perinatal period. Risk factors were: gestational age at 37completed weeks (adjusted Odds Ratio (aOR) 2.6, 95% Confidence Interval (CI) 1.6–4.3), male gender (aOR 1.4, 95% CI 1.01–1.9), South Asian ethnicity (aOR 3.6, 95% CI 1.6–8.4), African (aOR 3.5, 95% CI 1.9–6.5) and other non-Western ethnicity (aOR 1.9, CI 1.2–3.1). At 37 completed weeks gestation audit results showed that 26% of the women smoked, 91% were boys and in all but one case death occurred before birth. In 61% of all deceased SGA infants born at 37 completed weeks gestation referral from primary care by independent midwives to the obstetrician took place because of antepartum death before labor. Conclusions: Gestational age of 37 completed weeks, male gender, South Asian, African or other non-Western ethnicity and smoking are associated with perinatal mortality in SGA infants. These risk factors concern the complete term population starting at 37 weeks or even earlier. Therefore, it is of utmost importance to develop accurate diagnostic tests to screen for SGA before 36 weeks gestation to prevent perinatal mortality at term in SGA infants.